(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The world as a whole, experienced remarkable economic growth, technological development and scientific progress, but development has harmed the environment and now the environmental harm has been adversely affecting the development. This paper is an attempt to have an appraisal of watershed management for exploring its impact agricultural land use pattern in Thanagazi tehsil. Furthermore, the study aims to investigate rationally and objectively the dynamic nature of land use and agricultural land use pattern and its findings and queries to make useful suggestions for better crop pattern because the change in cropping pattern is the best indicator of socio-economic and cultural development of an area.